Partisipasi Masyarakat dalam Mendukung Lingkungan Bersih dan Sehat di Desa Baru Kecamatan Sinjai Tengah - Sitti Fatimah; Jusniaty Jusniaty; Syamsuddin Syamsuddin; Mukrimah Mukrimah (Journal of Government Insight, 2022)
This study aims to find out how public participation in support environment clean and healthy in the village New Subdistrict Central Sinjai . Study This using qualitative method . The results of the study indicate that community participation in supporting a clean and healthy environment in Baru Village, Central Sinjai District has not materialized as expected because of the five most prominent participations only in the form of mind participation and energy participation, while the participation that is very lacking is participation in the form of financial in the form of money. Thought participation This was realized in the meeting by providing some input to the Village Government regarding the efforts and steps needed to support a clean and healthy environment, one of which was proposing to make trash bins in every resident's house and proposed J clean activities. Employee participation is realized through community service activities every Sunday . Expert participation is realized through the participation of residents who have expertise such as masonry skills and expertise in the health sector. Goods participation is realized through the provision of goods from the community such as wood and bamboo, paint, cleaning tools as well as food and drinks for residents who take part in community service activities.